Liquid Biopsy of Extracellular Vesicle-Derived miR-193a-5p in Colorectal Cancer and Discovery of Its Tumor-Suppressor Functions - Wei, Rui; Chen, Lei; Qin, Da; Guo, Qingdong; Zhu, Shengtao; Li, Peng; Min, Li; Zhang, Shutian (Frontiers in Oncology, 2020)
Previously, abnormal extracellular vesicle (EV) sorting of miR-193a was identified in colorectal cancer (CRC) progression. Although a reduced level of miR-193a-5p in plasma/serum has been reported in many different types of cancer, the EV-derived miR-193a-5p level in CRC and its potential application as a minimal-invasive biomarker are still unknown. Here we evaluated the circulating EV-derived miR-193a-5p expression levels in a cohort of 101 participants by real-time quantitative polymerase chain reaction (RT-qPCR). We found that plasma EV-miR-193a-5p decreased significantly in CRC patients as compared to precancerous colorectal adenoma (CA) and non-cancerous control (NC) individuals. The circulating EV-miR-193a-5p showed an AUC of 0.740 in distinguishing CRC from CA, and an AUC of 0.759 in distinguishing CRC from NC. Furthermore, the suppression on CRC cells of miR-193a-5p was verified by transwell, MTS, EdU, RT-qPCR, and western blotting. Bioinformatic analysis predicted 32 genes, which were the most likely miR-193a-5p targeted and mainly focused on tumor progression. Among them, we revealed that miR-193a-5p could inhibit CRC migration and invasion via targeting tumor-associated genes like CUT-like homeobox 1 (CUX1) and Intersectin 1 (ITSN1). In conclusion, miR-193a-5p could suppress CRC development and decreased plasma EV-miR-193a-5p could be a promising biomarker for human CRC detection.